Development of Oil Palm Empty Fruit Bunch Cement Boards Based on Different Boards Surface Alteration - Karthikesh, Sharvvin Kumar; Nik Soh, Nik Zaini (Recent Trends in Civil Engineering and Built Environment, 2025)
The construction industry is currently dealing with a critical need to discover environmentally friendly alternatives to conventional building materials. Taking all of this into consideration, the application of agricultural waste in the production of cement-based boards has attracted major interest. This study focuses on the development of oil palm empty fruit bunch (OPEFB) cement boards through the application of different surface alteration techniques. The objective of this research is to the surface alteration method that can be applied for cement bonded fibre boards and evaluating the effect of surface alteration method on physical and mechanical properties of cement boards. There were two different approaches to the surface alteration that were used which is coating and sanding. The constant density and water content fixed as 1300 kg/m3 and 40% respectively. The mechanical properties, such as modulus of elastic, modulus of rupture and internal bonding while physical properties thickness monitoring and density have been specified to determine the potential of empty fruit bunch strength and to establish the research findings. The study’s findings revealed that varying the surface alteration techniques altered the mechanical and physical properties of the EFB cement board. Particularly, when compared to other surface alteration approaches, the board with coating method shown excellent mechanical and physical properties, with the MOR, MOE, IB, thickness swelling, and density produced being 4.434 N/mm2, 4236 N/mm2, 0.35 N/mm2,1.32%, and 1185 kg/m3 respectively. These findings highlight the potential of EFB as an environmentally friendly material for sustainable construction, providing benefits in terms of environmental preservation, energy conservation, and economic viability. These findings influenced the mechanical and physical characteristics of the EFB cement board.